Software Requirements for Complex Systems: Applying Design Science Research to a Requirements Elicitation Approach with the Functional Resonance Analysis Method (FRAM) - de Carvalho, Elaine (2022)
The requirement elicitation task is still considered critical, especially when dealing with complex (non linear) systems that need technological support with more resilient performance. That is, software capable of dealing with situations of uncertainty. The Functional Resonance Analysis Method (FRAM), based on Resilience Engineering concepts, is used to model the aspects associated with “work as done”, making the unpredictability of tasks more evident. This work, as an extended version of another article published in SBSI 2021, intends to detail aspects related to the application of Design Science Research in the projection of a heuristic model aimed at eliciting software requirements for complex systems as Healthcare supported by a computational tool, the ReqFRAM. Thus, it is intended to detail the steps for this study, the proposed heuristics, and their contributions to Requirements Engineering from the concepts of Resilience Engineering.